Judgement of the Constitutional Tribunal relating to an invalid regulation. A gloss to the decision of the Constitutional Tribunal of 30 October 2019, file no. P 1/18 (Journal of Laws, item 2196) - Tkaczyk, Edyta (The Opole Studies in Administration and Law, 2020)
The Constitutional Tribunal has ruled that a regulation which is no longer binding in the legal system – expires. By way of the Decision file no. P 1/18, Art. 57 § 5 point 2 of the Act dated 14 June 1960 – Administrative Procedure Code was found incompatible with the Constitution. These regulations are of historical character, although they were temporarily part of the legal system and could be adopted by the public authorities. The judgement was pronounced on 30 October 2019, that is after the amendment to this article had come into force. Irrespective of the legislator’s actions, the Constitutional Tribunal had to issue a judgment as a historical decision which is a logical principle elaborated on the basis of Art. 190 of the Constitution.